The Influences of Occupational Safety and Health Awareness Factors Among Workers: A Case Study in A Company in North Malaysia - Jaafar, Rosley; Ahmad, Muhammad Adi Ikhwan (Journal of Techno-Social, 2023)
Occupational Safety and Health (OSH) is an essential area that concerns the protection, health, and safety, including the welfare of people or workers in any type of employment. This study was conducted to identify the factors influencing the workers' awareness of OSH and the level of OSH awareness among the workers in a manufacturing company in northern Malaysia. The questionnaire was distributed to 60 employees manually and collected within one week. The Statistical Package for the Social Sciences (SPSS) version 20 was used to analyse the data and present it in descriptive statistics, which are in percentage, frequency, and mean. The results of this study found that the OSH awareness level is high with an average mean score of 4.23 and indicated that OSH policy is the highest influence factor with a mean score of 4.47, while the lowest is Safety and Health Committee (SHC) with a mean score of 3.87. The activities such as safety week, OSH awareness campaigns, accident prevention training, posters, and safety talks can raise awareness in the workplace and help workers achieve a higher level of OSH awareness. The purpose of the OSH activities is to reduce occupational injuries and illnesses and foster the development of a safe culture in the workplace. Hence, OSH training and practises are very important and the best way to educate and raise the OSH awareness of employers and employees.